Design, Implementation, and Evaluation of a Medical Education Fellowship Program for the Faculty Members of Kerman University of Medical Sciences Based on the Kirkpatrick Model - Zahra Fatahi; Zeynab Shakiba; Bahareh Bahman Bijari; Kambiz Bahaadinbeigy; Majid Fasihi Harandi; Mahla Salajegheh; Mahmoud Reza Dehghani (Kerman University of Medical Sciences, 2018)
Background Attempts to increase the development of faculty members can improve their ability to assume different roles. Objectives The purpose of this study was to design, implementation, and evaluation a medical education fellowship program for the faculty members of Kerman University of Medical Sciences and to propose practical recommendations for the future design of development programs. Methods In this semi-experimental study, a total of 53 faculty members of Kerman University of Medical Sciences participated in a one-year development program, which was designed by the Education Development Center and included the main disciplines of medical education. The program was evaluated in several steps, using the Kirkpatrick model. Results In the first level of Kirkpatrick model, the majority of the participants were satisfied with the general quality of the fellowship program. Based on the findings, the program led to an increase in the knowledge of faculty members and promoted a more positive attitude towards education and these programs. The findings related to the second level of Kirkpatrick model showed a significant difference between the pretest and posttest results (P < 0.05). In addition, analysis of the effects of the program on the participants' behaviors and practical learning indicated positive changes. Conclusions The medical education fellowship program led to positive changes in the participants' attitudes towards education and faculty development programs and increased their knowledge about educational principles and strategies and achieving of training skills. It can be concluded that the medical education fellowship program could achieve many of its preset goals.